KEMAMPUAN KEUANGAN DAN PAJAK DAERAH PROVINSI JAWA TENGAH (Proceeding Fakultas Ekonomi, 2013)
Act No. 28 of 2009 on Regional Tax and Levies entered into force in 2010 has two important considerations. The second thing to be considered the birth is: that the local taxes and levies is one important source of revenue to finance the implementation of local government and in order to improve service to the public and local independence, is necessary to expand the area to tax and levies and granting discretion in tariff setting. The aims of study to analyze the financial and tax areas of Central Java province. The parameters used are revenue performance calculation and analysis ( Regional Own Revenue / PAD ) and local taxes through Elasticity Size, Share, and Growth; data used in this study in the form of a data realization Central Java provincial budget in 2008 sapai to 2011 Results of this study found: 1. Revenue growth from year to year has increased, which in 2009 grew 8.15%, in 2010 grew 10.43% and 15.18% growth in 2011. 2. PADcontribution to the Revenue and Expenditure (Budget) for four consecutive years at the rate of 70%. 3. PAD Elasticity to the Gross Regional Domestic Product (GRDP) in 2009 of 0.85, 0.89 in 2010, and in 2011 at 1.25.Keywords: tax law, regional own revenue growth, share of regional own revenue, elasticity of regional own revenue.